The relationship between job satisfaction and organizational commitment among lecturers in Heilongjiang Province, China - Wang, Guixia; Basri, Ramli; Jusoh, Rosnani (Human Resource Management Academic Research Society, 2019)
This study investigates the relationship between job satisfaction and organizational commitment among the lecturers in Higher Educational Institutions (HEI) in Hei Long Jiang Province, China. From 2529 HEI in China, 83 of them are located in Heilongjiang province. Through simple random sampling, four HEI with total of 221 lecturers in Heilongjiang province took part in this study. This study revealed that the level of job satisfaction and organizational commitment of the lecturers were bordering on the low side. Results also show statistically significant differences between the mean scores of job satisfaction and organizational commitment in terms of gender, marital status, age, highest qualification, job position and years of teaching. Significant correlation was found between some dimensions of job satisfaction and organizational commitment. Implications on the management and recommendation of the studies were discussed thoroughly.